BEYOND TEST: ALTERNATIVES IN ASSESSMENT (A GLANCE OF THOUGHT FOR TECHNIQUES, CHALLENGES, AND OPPORTUNITIES DUE TO THE IMPLEMENTATION OF 2013 CURRICULUM) - Ni Luh Putu Eka Sulistia Dewi (Jurnal Bahasa Lingua Scientia, 2014)
The changes of curriculum influences the assessment procedure implemented in elementary and high schools in Indonesia education system. Traditional test is no longer becomes the primary assessment instrument since the focus of the assessment is on the students’ competence. Therefore, alternatives in assessment need to be put into consideration. The implementation of the alternatives assessment, such as portfolio, journal, and self and peer- assessment will bring their own challenges, and to face the challenges teachers need to broaden their insight on the opportunities that embedded on each alternative assessment techniques.